Incidence, natural course, and outcome of type II endoleaks in infrarenal endovascular aneurysm repair based on the ENGAGE registry data - Dijkstra, Martijn; Böckler, Dittmar (Journal of vascular surgery, 2020)
Objective - The purpose of this study was to report the incidence, natural history, and outcome of type II endoleaks in the largest prospective real-world cohort to date. - Methods - Patients were extracted from the prospective Endurant Stent Graft Natural Selection Global Postmarket Registry (ENGAGE). Two groups were analyzed: first, patients with an isolated type II endoleak; and second, patients with a type II endoleak who later presented with a type I endoleak. A health status analysis between patients with an early type II endoleak and patients with no endoleak was performed. Second, an attempt was made to identify risk factors in patients with a type II endoleak who later presented with a type I endoleak. - Results - Through 5 years of follow-up, a total of 197 (15.6%) patients with isolated type II endoleaks were identified. Most were detected within the first 30 days (n = 73 [37.1%]) and through the first year (n = 73 [37.1%]), with the remainder being detected after 1 year of follow-up (n = 51 [25.8%]). Patients with a type II endoleak had a higher incidence of aneurysm growth and more secondary endovascular procedures (15.4% vs 7.5% at 5 years; P < .001). Overall survival was higher in the isolated type II endoleak group compared with patients with no endoleak (77.2% vs 67.0% at 5 years; P = .010). Twenty-two patients (10%) with a type II endoleak were diagnosed with a late type I endoleak (type IA, n = 10; type IB, n = 12), with a secondary intervention rate of 67.5% through 5 years. There was no difference in health status scores between patients with an early type II endoleak and patients without any type of endoleak at 1-year follow-up. - Conclusions - In the ENGAGE registry, isolated type II endoleaks are present in 15.6% of patients during follow-up. The majority do not require secondary intervention, and an early isolated type II endoleak does not have an impact on health status through 1 year. However, a small group of patients with a type II endoleak will present with a type I endoleak, resulting in a high secondary intervention rate and significant risk of aneurysm-related complications.